The Efforts of the Indonesian Competition Commission to Seek Judicial Review of the Tender Case Decision for the Revitalization of Taman Ismail Marzuki III - Nurulhuda, Nada Syifa; Surahmad, Surahmad (UNIVERSITAS PAKUAN, 2025)
Abstract The case of the Revitalization of Taman Ismail Marzuki III with KPPU Decision No. 17/KPPU-L/2022 has given rise to legal uncertainty due to the dualism of Supreme Court cassation decisions: Decision No. 523K/Pdt.Sus-KPPU/2024, which annulled, and Decision No. 745K/Pdt.Sus-KPPU/2024, which upheld the ruling. This dualism not only obstructs execution but also undermines the authority of KPPU in enforcing competition law. This study aims to examine the legitimacy of KPPU in filing a Judicial Review (PK) and its implications for legal certainty and justice. The method applied is normative juridical with a statutory approach and judicial decision analysis. The findings show that Article 16 paragraph (2) of Supreme Court Regulation (Perma) No. 3 of 2021 bars KPPU from filing a Judicial Review, thereby depriving KPPU of legal certainty in executing its decisions, as the two rulings reflect a dualism. This study recommends the issuance of a new Supreme Court Regulation granting KPPU the authority to seek a Judicial Review to ensure justice and legal certainty in this case and in future cases. Keywords: KPPU, Judicial Review, Legal Certainty